Chemical Composition and Fatty Acid Contents of Chestnuts Grown in Bursa Province, Turkey - Öztürk, Serkan; Çetin, Murat; Çetin, Mehmet (Asian Journal of Chemistry, 2010)
In this study, some chemical properties such as moisture, protein, starch, invert sugar, sucrose, fat and fatty acid contents of chestnut types grown in Atatürk Central Horticultural Research Institute, Yalova were determined. Chestnut fruits from seven cultivars were harvested in October and stored as required during analysis. The analysis resulted in some variations that were 51.18 to 54.74 % of moisture, 5.35 to 8.17 % of protein, 81.06 to 94.21 % of total carbohydrate, 52.92 to 75.25 % of starch, 10.66 to 28.84 % of total sugar, 0.10 to 2.53 % of invert sugar, 8.05 to 27.04 % of sucrose and 0.90 to 2.47 % of fat. After the analysis of fat compositions, chestnuts were found rich in unsaturated fatty acids of which linoleic acid was the highest and varied from 38.03 to 53.23 %. While oleic acid was the second highest unsaturated fatty acids varying from 20.02 to 36.64 %, palmitic acid was the highest among saturated fats and varied from 13.27 to 17.14 %.